1999
DOI: 10.1088/0953-4075/32/17/318
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and total cross sections for electron-carbon dioxide collisions in the intermediate energy range

Abstract: In this work, we report on a joint theoretical and experimental investigation on electron-CO 2 collisions in the intermediate energy range. More specifically, the elastic differential, integral and momentum transfer cross sections as well as the grand total (elastic+inelastic) cross sections in the 30-500 eV energy range are calculated and reported. A complex optical potential consisting of static, exchange, correlation-polarization plus absorption contributions is used for the description of the electron-mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 52 publications
5
23
0
Order By: Relevance
“…At 30, 40, and 50 eV,t he DCS measurements of Gibson et al [1999], Kanik et al [1989], and Tanaka et al [1998] are in reasonable accord, within the uncertainties of each measurement, and at 50 eV the DCS of Gibson et al [1999] and Register et al [1980] arec onsistent. At 100 eV,t he measured DCS values of Iga et al [1999] are in good agreementw ith Kanike ta l. [1989] and Tanaka et al [1998].…”
Section: Elastic 221 Differential Elasticsupporting
confidence: 79%
“…At 30, 40, and 50 eV,t he DCS measurements of Gibson et al [1999], Kanik et al [1989], and Tanaka et al [1998] are in reasonable accord, within the uncertainties of each measurement, and at 50 eV the DCS of Gibson et al [1999] and Register et al [1980] arec onsistent. At 100 eV,t he measured DCS values of Iga et al [1999] are in good agreementw ith Kanike ta l. [1989] and Tanaka et al [1998].…”
Section: Elastic 221 Differential Elasticsupporting
confidence: 79%
“…The elastic scattering (Graph 43) and momentum transfer (Graph 44) cross sections were measured by Register et al [40] in the energy range 4-50 eV and by Iga et al [41,42] in the high energy region 100-1000 eV with an estimated uncertainty of ±20%. Tanaka et al [43] reported both cross sections in the energy range 1.5-100 eV.…”
Section: Carbon Dioxide Moleculementioning
confidence: 99%
“…In our calculation, the absorption effects are taken into account via the use of a complex optical potential to describe the dynamics of the e − -SO 2 interaction, whereas a combination of the iterative Schwinger variational method (ISVM) [30,31] and the distorted-wave approximation (DWA) [32,33] is used to solve the scattering equations. This procedure has been successfully applied to treat electron scattering by a number of molecules [34][35][36][37]. Although the present method is unable to calculate TICS directly, our calculated TACS provide an estimate of the contributions of all inelastic collisions, including both excitation and ionization processes.…”
Section: Introductionmentioning
confidence: 99%